ENHANCING MSME FINANCIAL REPORTING IN EAST JAVA: THE ROLE OF MENTORSHIP - Eny Zuhrotin Nasyiah; Umi Nandiroh (EKUITAS (Jurnal Ekonomi dan Keuangan), 2024)
This study investigates how mentoring, financial inclusion, and financial literacy dynamics affect the calibre of financial reporting among East Javan MSMEs. Data was gathered quantitatively by surveying 210 MSME owners from various business levels and industrial sectors. Random sampling was used to guarantee the analysis's representativeness. The findings show a strong correlation between mentoring, financial inclusion, financial literacy, and the calibre of MSME financial reporting. Accuracy and timeliness of financial reporting were positively impacted by high financial literacy and inclusion and excellent mentoring. The findings highlight how crucial these elements are to improving the calibre of MSME financial reporting and providing insightful information to financial institutions and policymakers. As a result, improving MSME accountability, transparency, and overall financial management can be significantly assisted by specific measures, including financial literacy and mentorship programs. Stakeholders may help improve financial reporting procedures, which are critical to the long-term viability and expansion of MSME, by tackling these issues. This study addresses a foundation for developing more effective plans to improve MSME financial reporting in East Java and other areas.